Pengaruh Kualitas Produk Dan Inovasi Produk Terhadap Keputusan Pembelian Sepatu Compass Pada Mahasiswa Di Jakarta - Putra, Muhammad Adriyan; Iskandar, Donant Alananto (Research and Community Service UNIVERSITAS KALBIS, 2024)
A product is anything that can be offered to a market for attention, acquisition, use, or consumption that can satisfy a consumer want or need. The problem in this research is to determine purchasing decisions in the shoe industry, especially Compass shoes. For this reason, the method chosen in this research is quantitative with the help of surveys carried out in the data collection process. The results of this research reveal that: (1) there is a positive and significant influence between the product quality variable on the decision to purchase Compass shoes among students in Jakarta, (2) there is a positive and significant influence between the product innovation variable on the decision to purchase Compass shoes among students in Jakarta, (3) there is a positive and significant influence jointly between product quality and product innovation variables on the decision to purchase Compass shoes among students in Jakarta.